Spore 192: Digitalising agriculture - Bridging the gender gap - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2019)
Access to digital innovations – from SMS advice services to digital networks that connect women in agribusiness – is enabling women to participate in formal agricultural value chains and improve their livelihoods.